Kaempferol Alleviates Steatosis and Inflammation During Early Non-Alcoholic Steatohepatitis Associated With Liver X Receptor α-Lysophosphatidylcholine Acyltransferase 3 Signaling Pathway - Xiang, Hongjiao; Shao, Mingmei; Lu, Yifei; Wang, Junmin; Wu, Tao; Ji, Guang (Frontiers in Pharmacology, 2021)
BACKGROUND: Kaempferol (KP) has a variety of biological effects such as anti-inflammatory, anti-oxidant, anti-aging and cardiovascular protection. However, it is unclear on the mechanism of KP in the treatment of non-alcoholic steatohepatitis (NASH). AIM: This study aims to explore the mechanism of KP in the treatment of NASH through in vivo and in vitro experiments. METHODS: (1) In vivo experiment: In the C57BL/6 NASH mice model induced by high fat diet (HFD), KP was administered by gavage at a dose of 20 mg/kg/day. (2) In vitro experiment: Palmitic acid/Oleic acid (PA/OA, 0.375/0.75 mM) was used to intervene HepG2 and AML12 cells to establish a steatosis cell model. Three concentrations of KP, low (20 μmol/l), medium (40 μmol/l) and high (60 μmol/l) were used in vitro. The mRNA and protein expression of related molecules involved in LXRα-LPCAT3-ERS pathway were detected using RT-PCR and Western blot. RESULTS: In the NASH mice model, KP can significantly reduce the expression of LXRα, LPCAT3 and ERS-related factors PERK, eIF2α, ATF6, ATF4, XBP1, CHOP, IRE1α and GRP78. In the model of steatosis cells, KP could decrease the content of triglyceride and lipid droplets, and also decrease the expression of LXR α, LPCAT3 and ERS related factors PERK, eIF2α, ATF6, ATF4, XBP1, CHOP, IRE1α and GRP78. CONCLUSION: KP may decrease the expression level of LXRα and LPCAT3, thus improve ERS and reduce hepatic steatosis and inflammation.